(untitled) (Per Musi, 2021)
Urban public art is an art exhibition held in public places, contextualized with their surroundings and its audience. Technology is a significant trend in public art due to its connection possibilities with human life, fostering different kinds of interaction. In this way, this work presents an installation proposal consisting of an environment for creating collaborative random music from interaction with mobile devices in public spaces. Everyone participating in the installation is a composer and interaction is a chance agent, although it follows John Cage’s composition methods. In order to probe technology, we carried out two pilot studies, followed by a workshop for the installation itself. Those two pilot studies led us to a new version that was put into practice during the workshop. During the workshop, participants’ interaction generated fourteen compositions, and the sounds resulting from the collaborative composition were made available to the public through a website.